2018
DOI: 10.1109/tvt.2017.2758581
|View full text |Cite
|
Sign up to set email alerts
|

Forward Collision Vehicular Radar With IEEE 802.11: Feasibility Demonstration Through Measurements

Abstract: Abstract-Increasing safety and automation in transportation systems has led to the proliferation of radar and IEEE 802.11p-based dedicated short range communication (DSRC) in vehicles. Current implementations of vehicular radar devices, however, are expensive, use a substantial amount of bandwidth, and are susceptible to multiple security risks. In this paper, we use the IEEE 802.11 orthogonal frequency division multiplexing (OFDM) communications waveform, as found in IEEE 802.11a/g/p, to perform radar functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 43 publications
0
53
0
Order By: Relevance
“…Dual-functional radarcommunication in mmWave systems is a new and promising research area. Recent treatises [92]- [94] propose to invoke the radar function to support V2X communications based on the IEEE 802.11ad WLAN protocol, which operates in the 60GHz band. As the WLAN standard is typically indoor based and employs small-scale antenna arrays, it can only support short-range sensing at the order of tens of meters.…”
Section: Limitations Of the Existing Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-functional radarcommunication in mmWave systems is a new and promising research area. Recent treatises [92]- [94] propose to invoke the radar function to support V2X communications based on the IEEE 802.11ad WLAN protocol, which operates in the 60GHz band. As the WLAN standard is typically indoor based and employs small-scale antenna arrays, it can only support short-range sensing at the order of tens of meters.…”
Section: Limitations Of the Existing Workmentioning
confidence: 99%
“…While the proposed approaches in this paper focus on mmWave cellular systems, it can be extended to V2X applications with the consideration of specific channel models for vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) scenarios. Again, such schemes call for the design of novel beamforming/signaling approaches [92], [93], [116].…”
Section: ) Dfrc For V2xmentioning
confidence: 99%
“…where · is a Euclidean norm. It is shown that (14) has the same structure as (12). Last, the origins of all paths {(x p , y p )} can be computed using the parameters {z * , ω * } as illustrated in (E1).…”
Section: )mentioning
confidence: 99%
“…VANET correspondences are grouped into V2I (Vehicle to Framework), Hybrid (V2I and V2V) and V2V (Vehicle to Vehicle). V2I deals with information exchange amid road side units (RSU) and automobiles (Daniels et al, 2018). A V2I framework is being modelled in (Punia and Kumar, 2018) and the effect of mobility on QoS parameters is analysed.…”
Section: Literature Review On Vanetsmentioning
confidence: 99%